Tecnologia 5G NR e suas aplicações no ramo do agronegócio - Santos, Maria Victória Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Daily, the demand for cell phones and mobile internet is increasing all over the world and, as this demand increases, so does the need for a new technology to overcome the requirements of previous networks. The fifth generation of mobile networks (5G) emerges with the objective of revolutionizing mobile communications and providing improvements in the mobile broadband segment, in addition to offering new applications that will benefit other segments, such as applications in ultra-reliable low-latency communication and in massive IoT communication. This project work aims to present the 5G NR technology, addressing its theoretical aspects, in order to understand the operation of this technology through its enabling technologies (Small Cells, Beamforming, Massive MIMO and others), which make possible the requirements of ultra-low latency and high reliability, high capacity and more. In addition, the following project also intends to expose the current situation in Brazil and in the world in the scenario of 5G deployment, as well as the main difficulties encountered in Brazil for the deployment and consolidation of the technology. Finally, the project work aims to present some IoT applications that will be possible with 5G. In Agribusiness, which represents 26,1% of Brazilian GDP (Gross Domestic Product), 5G technology has great potential to impact this industry, which still suffers from a lack of connectivity. Therefore, this segment was chosen to be the focus of the present study. At the end of this project work, it will be possible to conclude that 5G technology is already a reality and is moving towards its full operation in Brazil. Furthermore, this technology corroborates the advent of digital transformation, which in the future will be part of everything that surrounds humanity.

Diariamente, a demanda por celular e internet móvel vem aumentando em todo o mundo e, ao passo que esta demanda aumenta, aumenta-se também a necessidade de uma nova tecnologia, a fim de superar os requisitos das redes precedentes. A quinta geração de redes móveis (5G) surge, então, com o objetivo de revolucionar as comunicações móveis e proporcionar melhorias no segmento de banda larga móvel, além de oferecer novas aplicabilidades que beneficiarão outros segmentos, como as aplicações em comunicação ultra confiável de baixa latência e as aplicações de comunicação de IoT massivo. Este trabalho tem como objetivo apresentar a tecnologia 5G NR, abordando seus aspectos teóricos, a fim de se compreender o funcionamento desta tecnologia por meio de suas tecnologias habilitadoras (Small Cells, Beamforming, Massive MIMO e outras), e que tornam possíveis os requisitos de baixíssima latência e alta confiabilidade, alta capacidade e muito mais. Além disso, o trabalho a seguir também pretende expor a situação atual do Brasil e do mundo no cenário de implantação do 5G, bem como as principais dificuldades encontradas no Brasil para a implantação e consolidação da tecnologia. Por fim, o trabalho visa apresentar algumas aplicações de IoT que serão possíveis com o 5G. No campo do Agronegócio, que representa 26,1% do PIB brasileiro, a tecnologia 5G tem grande potencial de impactar nesta indústria, que ainda sofre com a falta de conectividade. Portanto, este segmento foi escolhido para ser foco do presente estudo. Ao final, será possível concluir que a tecnologia 5G já é uma realidade e vem caminhando para sua plena operação no Brasil. Ademais, esta tecnologia corrobora o advento da transformação digital, que futuramente fará parte de tudo o que rodeia a humanidade.
5G NR technology and its applications in the agribusiness sector
Keywords: Mobile Internet; Technology; Telecommunications; Internet of Things; Agribusiness; 5G; Internet Móvel; Tecnologia; Telecomunicações; Agronegócio; Telefonia celular; Internet das coisas